2009
DOI: 10.1186/1471-2350-10-2
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method for detection of five known mutations associated with aminoglycoside-induced deafness

Abstract: Background: South Africa has one of the highest incidences of multidrug-resistant tuberculosis (MDR-TB) in the world. Concomitantly, aminoglycosides are commonly used in this country as a treatment against MDR-TB. To date, at least five mutations are known to confer susceptibility to aminoglycoside-induced hearing loss. The aim of the present study was to develop a rapid screening method to determine whether these mutations are present in the South African population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 21 publications
0
41
0
5
Order By: Relevance
“…The SnapShot technique can detect the 6 known mutations in a single reaction. 5,6 The t-test two-sample assuming unequal variances test was used to calculate the difference in the mean ages between HIV-positive and HIV-negative patients with hearing loss at a 95% confidence interval (CI). The odds ratio (OR) (95% CI) was used to calculate the measure of association of HIV and aminoglycoside-induced hearing loss.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SnapShot technique can detect the 6 known mutations in a single reaction. 5,6 The t-test two-sample assuming unequal variances test was used to calculate the difference in the mean ages between HIV-positive and HIV-negative patients with hearing loss at a 95% confidence interval (CI). The odds ratio (OR) (95% CI) was used to calculate the measure of association of HIV and aminoglycoside-induced hearing loss.…”
Section: Methodsmentioning
confidence: 99%
“…This study was divided into 2 parts of which the first relates to prevalence of the 6 known aminoglycoside-induced deafness mutations in the MT-RNR1 gene in a cohort of MDR-TB patients. 5,6 Although these data have been published, they are cited where referred to in the text for completeness. The second part involves prospective hearing evaluation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently a number of genes have been identified that show a strong association with aminoglycoside-induced hearing loss [69][70][71][72][73]. These genes are uncommon, however, occurring in ,1% of those tested in a South African population [70].…”
Section: Managing Hearing Lossmentioning
confidence: 99%